The effects of the CLA 1956 on judicial discretion, quantum of damages and interest on damages in personal injury and fatal accident claims arising out of motor vehicle accidents : A critical appraisal / Nazli Binti Mahdzir - Mahdzir, Nazli (2014)

(untitled)
Sections 7, 8 and 28A of the Civil Law Act 19561 are enacted to regulate the assessment of damages for personal injury and fatal accident claims arising out of motor vehicle accidents. The provisions aim to control the quantum of damages being meted out by the courts. Despite the good intention of the legislature, the provisions have been viewed with disfavour by many as a legislative attempt to reduce the quantum of damages and/or fetter or worst still, to divest the judiciary of their discretion in the assessment of damages. The actual impacts on judicial discretion and the quantum of damages are however yet to be fully worked out. Therefore, this research is to be welcomed as it seeks to critically appraise the actual effects of sections 7, 8 and 28A of the CLA 1956 on the exercise of judicial discretion and the quantum of damages being awarded by the courts. The same critical appraisal is also extended to section 11 of the CLA 1956, the court rules relating to the assessment of interest on damages as well as the provisions relating to the assessment of damages in Singapore and Brunei. This research applied both the descriptive and analytical approach. Malaysian data have been collected from primary and secondary sources together with interviews with legal practitioners and representatives from several Malaysian insurance companies. This research began with the proposition that despite the provisions in the CLA 1956 and court rules, judges in Malaysia still retain their discretion (albeit with statutory interventions) in assessing damages and interest on damages for personal injury and fatal accident claims arising out of motor vehicle accidents. It concluded that sections 7, 8, 11, 28A of the CLA 1956 and Order 42 Rule 12 of the Rules of Court have resulted in mixed effects on the judges’ discretionary power; total abolition of discretionary power, maintaining the discretionary power as it was before the 1984 amendments, maintaining the discretionary power but with restrictions and mere codification of existing practices. The research also provides several suggestions for statutory amendment in order to rectify the problems with sections 7, 8, 11, 28A of the CLA 1956 and Order 42 Rule 12 of the Rules of Court 2012. The suggested amendments are also necessary to ensure damages and interest awarded for personal injury and fatal accident claims arising out of motor vehicle accidents is consistent, fair and reasonable to the claimants while affordable to the insurance industry.